Yearbook for Eastern and Western Philosophy (De Gruyter, 2016)
The Yearbook for Eastern and Western Philosophy is a forum for philosophers and academics from China, Germany, and Europe. It facilitates exchange between academic cultures and develops joint fields of research while also consolidating and coordinating social-scientific ties and research projects. A focus is placed on Eastern and Western philosophical traditions as well as on topics in religious studies, cultural studies, politics, and law.